Answer:
Third choice 7(x + 2) - 3x = 2/3(6x + 3)
Explanation:
Choice answer 1 has infinitely many solutions since -1/2(8x + 6) - 2x = -3(2x + 1) → -6x - 3 = -6x - 3 = 0 → 0 = 0 [is always equal to].
Choice answer 2 has one solution since
-1/2(8x + 6) - 2x = -3(2x + 1) → -2x - 8 = 2x - 8 → x = 0 [is equal to in 1 condition].
Choice answer 3 has no solution since
7(x + 2) - 3x = 2/3(6x + 3) → 4x + 14 = 4x + 2 → 0 = -12 [is never equal to].
Choice answer 4 has infinitely many solutions since -2x + 5 - 3x + 12 = -5(x - 3) + 2 → -5x + 17 = -5x + 17 → 0 = 0 [is always equal to].